Responsiveness to the Elderly Health Care Services of the Local Fund in the National Health Security Scheme, Phothalae District, Phichit Province - เนียมจันทร์, ปาจรีย์; บุญธรรม, อังสนา; เจริญกุล, ชนินทร์; วรารักษ์, อัจฉรา (Journal of Health Science of Thailand, 2021)
This mixed methods research investigated the responsiveness to the elderly health care services of local fund in the National Health Security Scheme, Phothalae District, Phichit Province. The samples of this study included 6 individuals comprising of the fund committees, representatives of local administrative organizations and people sector, and public health officers from 2 funds, as well as 396 elderly people. Data were collected using in-depth interview, related documents and structured interview; and were analyzed by using content analysis and descriptive statistics-number, percentage, and mean. The results showed that the process of fund planning using participatory community analytical tools to diagnose the cause of the problems by implementing the elderly program and related projects led to the elderly health care service provision according to their right as well as the needs of well elder, home bound and bed bound groups. Some activities had relatively low responsiveness because there were no services such as smoking and alcohol drinking screening test activities (47.8%), oral health screening activities (37.7%), assessing the ability of daily living activities (42.6%), home visiting activities (48.7%), physiotherapy-based rehabilitation activities (80.0%) and rehabilitation activities by traditional medicine (78.9%). In addition, some activities were not accomplished by the elderly who were employed, that led to the elderly not receiving health care service in accordance to their right, and those activities included health behavior adjustment activities and exercise (38.1%), health promoting activities using Thai traditional medicine (35.40%), promoting health innovation activities with local wisdom (38.3%) and examination of eyes, kidney, foot complications activities (27.30%). The suggestions of this study included the improvement of follow-up and proactive communication skills of public health volunteer teams and public health officers for follow-up and proactive communication; and the information system for the elderly should be developed.